Attitudes and Willingness to Assume Risk of Experimental Therapy to Eradicate Genital Herpes Simplex Virus Infection - Oseso, Linda (Sex Transm Dis, 2016)
BACKGROUND: Current treatment of genital herpes is focused on ameliorating signs and symptoms but is not curative. However, as potential HSV cure approaches are tested in the laboratory, we aimed to assess the interest in such studies by persons with genital herpes, and the willingness to assume risks associated with experimental therapy. METHODS: We constructed an anonymous online questionnaire that was posted on websites that provide information regarding genital herpes. The questions collected demographic and clinical information on adults who self-reported as having genital herpes, and assessed attitudes toward and willingness to participate in HSV cure clinical research. RESULTS: 711 participants provided sufficient responses to be included in the analysis. 66% were women; the median age was 37 years, and the median time since genital HSV diagnosis was 4.7 years. The willingness to participate in trials increased from 59.0% in Phase 1 to 68.5% in Phase 2 and 81.2% in Phase 3 trials, and 40% reported willingness to participate even in the absence of immediate, personal benefits. The most desirable outcome was the elimination of risk for transmission to sex partner or neonate. The mean perceived severity of receiving a diagnosis of genital HSV-2 was 4.2 on a scale of 1 to 5. CONCLUSIONS: Despite suppressive therapy available, persons with genital herpes are interested in participating in clinical research aimed at curing HSV, especially in more advanced stages of development.